Hubungan Pola Asuh Orang Tua Dan Lingkungan Sekolah Dengan Self Disclosure Pada Siswa di MTS Al-Ikhlas Sukaluyu Cianjur Tahun 2022 - Echa Firda Salsabilla Zahrani; Mustopa Mustopa; Marisca Agustina (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Parenting relationships in the family have a very influential role in improving and changing children's behavior, especially in the level of self-disclosure. Another factor that causes or influences self-disclosure on students is the school environment. A good school environment can make children's behavior open. Likewise, if the school environment is not good, it will have an impact on the child's own behavior and make children less open. Purpose: to find out whether there is a relationship between parenting styles and the school environment with self-disclosure to students at MTS Al-Ikhlas Sukaluyu Cianjur. Type of research: This research is a quantitative study with a sample of 77 students in grades 7, 8 and 9 students of MTS Al-Ikhlas Sukaluyu who were made research respondents. The sampling technique is: simple random sampling and the design used in this study is a correlation with a cross-sectional approach. Results: Found the results of univariate analysis of parenting parents with a good category of 51 (67.1%) and school environment with a good category of 51 (67.1%), self-disclosure in students with a good category of 45 (59.2%) %). The results of multivariate analysis on parenting parents obtained a sign value. 0.782 > 0.05 and a correlation value of 0.32 means that there is no relationship between parenting style and self-disclosure. Then for the school environment and self-disclosure there is a Sign value. 0.052 > 0.05 and a correlation value of 0.224 means that there is no relationship between the school environment and self-disclosure.